THE EFFECT ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON ENVIRONMENTAL PERFORMANCE (LECTURER RESEARCH AT POLYTECHNIC LP3I JAKARTA) - Euis Winarti, Henita Rahmayanti, Mieke Miarsyah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The research objective was to determine the effect of organizational culture and work motivation on the lecturer performance environment. The sampling technique in this study is a probability sampling technique. The number of samples is 109 lecturers from the LP3I Jakarta Polytechnic. This research is a causal associative study with a quantitative approach to research data analysis using path analysis. The research results prove that; the direct effect organizational culture toward the lecturerenvironmental performance; the direct effect work motivation toward the lecturer environmental performance; organizational culture has an indirect effect through work motivation on lecturers' environmental performance. Lecturer environmental performance can be done by increasing organizational culture and work motivation. Organizational culture is not the only one that affects the environmental performance of lecturers, but work motivation need to be considered. The organizational culture and work motivation of the LP3I Jakarta Polytechnic lecturers have been applied in everyday life on campus.